Tax effects on share prices in uniquely different tax regimes - Selamat, Aslam Izah (2013)
This thesis is about a research to identify tax effect on share prices. Literatures on tax effect have been extended by several classic contributions in financial economics. The original studies were analytical studies attributed as the most widelyacknowledged classic articles appearing in print over 1958-1973 by Miller-Modigliani, Brennan, Litzenberger-Ramaswamy and Elton-Gruber. Although the tax effect research has been investigated and extended from many perspectives for more than five decades, there is no unanimity of findings up to this date, regarding the effect of tax on cash dividends or on share prices as tested using after-tax equilibrium theories developed by those early researchers. It is worthwhile to revisit this topic on two grounds. Databases available at present cover markets with unique-tax regimes in pretty underdeveloped and inefficient markets. These markets include tax-exempt regimes: Saudi Arabia, where neither dividend tax nor capital gain tax is applied. Other markets are Qatar and Kuwait,which apply only corporate tax on foreign-owned firms. Also, the topic is so central to corporate finance that it deserves a more careful attempt to isolate the impact of tax on share values, using more accurate test methodologies that were unavailable to early researchers. Using the widely-entrenched event study, some major dividend tax law changes in different tax regime countries are examined: (1) Malaysia and Singapore dividend tax elimination, which previously apply partial imputation taxation, (2) the US dividend tax cut, which previously applies double taxation. In both cases, we have found positive tax effect arising from a reduction/elimination of dividend tax, leading to increasing cash flows for investors. Also, we investigate the corporate tax law changes in China and Oman; these markets also indicate significant changes following the tax announcement. Further examination at the ex-dividend days share price behaviour at different tax regimes: the US, Malaysia and Singapore, we find significant difference after the tax law have taken into place, consistent with the Elton-Gruber proposition. Analysis at the tax-exempt countries in some Middle-Eastern countries also provides similar indications of tax explanation. With these sample markets, we have revealed a modest but clear support for tax hypotheses since the countries chosen for this research provides classic conditions of a controlled experiment.